2010
DOI: 10.1007/s10162-009-0205-8
|View full text |Cite
|
Sign up to set email alerts
|

cAMP-induced Auditory Supporting Cell Proliferation is Mediated by ERK MAPK Signaling Pathway

Abstract: Sensorineural hearing deficiencies result from the loss of auditory hair cells. This hearing loss is permanent in humans and mammals because hair cells are not spontaneously replaced. In other animals such as birds, this is not the case. Damage to the avian cochlea evokes proliferation of supporting cells and the generation of functionally competent replacement hair cells. Signal transduction pathways are clinically useful as potential therapeutic targets, so there is significant interest in identifying the ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…We found that after STOX1 knockdown in cultured epithelial cells, expression of markers for proliferation (PCNA and cyclin A, cyclin E) (26,42) was significantly reduced, but up-regulated following STOX1 over-expression. During mammalian organogenesis, the AKT pathway regulates both cell proliferation and programmed cell death (11,43). Our results further show that shSTOX1 inhibited phosphorylation of AKT in the inner ear utricular epithelial cells, while over-expression of STOX1 activated phosphorylation of AKT.…”
Section: Discussionsupporting
confidence: 71%
“…We found that after STOX1 knockdown in cultured epithelial cells, expression of markers for proliferation (PCNA and cyclin A, cyclin E) (26,42) was significantly reduced, but up-regulated following STOX1 over-expression. During mammalian organogenesis, the AKT pathway regulates both cell proliferation and programmed cell death (11,43). Our results further show that shSTOX1 inhibited phosphorylation of AKT in the inner ear utricular epithelial cells, while over-expression of STOX1 activated phosphorylation of AKT.…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, the Raf kinases play an important and specific role in the activation of the MAPK/ERK cascade 36 . For example, B-RAF can be activated by the cAMP/PKA pathway, which leads to increases in the levels of ERK-1/2 activity in supporting cells expressing B-Raf in the avian auditory epithelium 37 . The elevated expression levels of cAMP and B-Raf have been reported to increase the levels of cell proliferation in cultured neuronal cells 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Inner sulcus cells might provide some surviving factors to adjacent IHCs. In contrast, the MEK/ERK pathway was likely to be involved in the cell cycle promotion of the Hensen's and Claudius' cells for two reasons: p-ERK was detected in the Hensen's and Claudius' cells ( Figure 3F) in which BrdU uptake and pHH3 were also detected, and the activation of MEK/ERK pathway causes the proliferation of SCs in the chicken basilar papillae, resulting in the regeneration of HCs (Bell and Oberholtzer, 2010).…”
Section: Discussionmentioning
confidence: 99%